Novel cytomorphologic characteristics suggesting human papillomavirus infection in patients diagnosed as negative for intraepithelial lesion or malignancy and a comparison of diagnostic performance of three human papillomavirus tests. Issue 10 (25th August 2018) - Jin, Min‐Sun; Lee, Hyebin; Kim, Min A.; Park, In Ae; Lee, Chul; An, Hyoung Jin; Shim, Bobae; Moon, Ji Hye; Won, Jae Kyung; Ryu, Han Suk
Abstract : Background: Although the Papanicolaou (Pap) test is the first‐line screening method for cervical cancer, it has low sensitivity for detection of human papillomavirus (HPV)‐infected cervical lesion compared to the HPV test. The aims of this study are to determine novel cytomorphologic parameters for HPV infection in patients previously diagnosed as negative for intraepithelial lesion or malignancy (NILM) and to comparatively analyze the detection performance of 3 HPV tests: nested PCR, the DNA Chip test, and the Liquid Beads Microarray (LBMA) assay. Methods: In total, 232 patients diagnosed with NILM were enrolled and assessed using 8 cytomorphologic parameters. Results: Six non‐classical cytomorphologic features were identified as novel characteristics suggesting HPV infection in patients initially diagnosed with NILM. A combination of these 6 variables showed the best predictive performance for HPV infection (area under the curve, 0.722). In terms of diagnostic ability, the LBMA assay showed better performance in detection of HPV infection (39.7%) in NILM cases compared to the other tests. Conclusions: Our results suggest that the novel cytomorphologic features used in this study can be used as supportive morphologic parameters to increase the sensitivity of cytological screening tests. The LBMA assay could be used as an advanced method for HPV detection.